Behaviour of Gypsum Plasterboards Under Mechanical Loads and Thermal Effects - Al-Sibahy, Adnan; Tarish, Ahmed (International Journal of Engineering and Technology, 2018)
This paper presents an experimental study conducted to investigate the behaviour of gypsum plasterboard assemblies subjected to mechanical loads and thermal effects. These assemblies were boxes in shape and connected to reinforced concrete slabs. Each side of gypsum plasterboard was fastened using either two or three bolts. The loads were applied at the assembly centre and the maximum flexural load at failure was recorded. Besides, the elapsed time to failure was monitored.The results obtained showed that the material property of the plasterboard and the method of fastening are governed the global behaviour of the tested samples. The average flexural braking loads at failure were 538 N and 564 N for the assemblies fastened with two and three bolts, respectively. The correspondingÂ failure times under conditions of fire exposure and mechanical loading were 2.1 minutes and 1.7 minutes, respectively. Suitable emended were made for the expressions suggested by the related codes of practice in order to suit the experimental resultsÂ Â